Pemetaan Potensi Lingkungan sebagai Sumber Daya Wisata di Desa Marga Sungsang, Banyuasin, Sumatera Selatan - Adriani, Hanni; -, Nurbaeti; Wibowo, Djoni; Maryam, Hanna; Baskoro, Harkyo Hutri (Jounal of Enviromental Science Sustainable, 2021)
Background: The planning and development of "Tourism Villages" in Indonesia is currently being carried out in various regions, both in cities/districts from Sabang to Merauke. This is in line with the program and support from the Ministry of Tourism and Creative Economy of the Republic of Indonesia which is always innovating, providing support and assistance to improve not only the community's economy but also the quality of Human Resources (HR) of the community in tourist villages. Marga Sungsang Village is one of the villages in Banyuasin II District which will be developed into a Tourism Village. This village, which is a fishing village, has environmental potential that can be used as a source of tourist attraction. This study aims to map the potential of environmental tourism resources in the village of Marga Sungsang. Methods:The research method used in this research is qualitative and spatial with a descriptive approach. The data collection method used is by observing the potential of environmental tourist attraction data and mapping tourism potential spatially with the Geographical Information System (GIS). Results: The results showed that the distribution of potential tourist attractions in Marga Sungsang Village consisted of the potential for natural, cultural, culinary, and architectural tourism. Conclusions: The map of the distribution of tourist attractions that is processed with GIS can be used as a base map in making a tourism map and making tourism planning based on environmental potential resources.